Heteroatom Functionalization of H‑Terminated Diamond Surfaces - Li, Chenxi; Oliveira, Eliezer F. [UNESP]; Biswas, Abhijit; Puthirath, Anand B.; Zhang, Xiang; Pramanik, Atin; Garratt, Elias J.; Neupane, Mahesh R.; Pate, Bradford B.; Birdwell, Anthony Glen; Ivanov, Tony G.; Terlier, Tanguy; et al. (American Chemical Society (ACS), 2023)
Diamond surface functionalization has received significant research interest recently. Specifically, H-termination has been widely adopted because it endows the diamond surface with negative electron affinity and the hole carrier is injected in the presence of surface transfer dopants. Exploring different functional groups' attachment on diamond surfaces and their impact on the electronic structure, using wet and dry chemical approaches, would hence be of interest in engineering diamond as a semiconductor. Here, we report the functionalization of the H-terminated diamond surface with nitrogen and sulfur heteroatoms. Surface characterization of functionalized diamond surfaces shows that these groups are well-distributed and covalently bonded to diamonds. Four chemical functional groups (-SH, -S-S-, -S-O, and -S=O) were found on the sulfurized diamond surface, and two groups (-NH2 and =NH) upon amination. We also report co-functionalization of surface with N and S (N-S), where sulfurization promotes sequential amination efficiency with reduced exposure time. Electrical measurement shows that heteroatom-modified diamond surfaces possess higher conductivity than H-terminated diamonds. Density functional theory (DFT) shows that upon functionalization with various N/S ratios, the conduction band minimum and valence band maximum downshift, which lowers the bandgap in comparison to an H-terminated diamond. These observations suggest the possibility of heteroatom functionalizations with enhanced surface electrical conductivity on the diamond that are useful for various electronic applications.